Comparison of the anaesthetic efficacy of different volumes of 4% articaine (1.8 and 3.6 mL) as supplemental buccal infiltration after failed inferior alveolar nerve block. (18th April 2014) - Singla, M.; Subbiya, A.; Aggarwal, V.; Vivekanandhan, P.; Yadav, S.; Yadav, H.; Venkatesh, A.; Geethapriya, N.; Sharma, V.
Abstract Aim To compare the anaesthetic efficacy of different volumes (1.8 mL vs. 3.6 mL) of 4% articaine with 1 : 100 000 epinephrine injected as buccal infiltrations after a failed inferior alveolar nerve block (IANB) in patients with symptomatic irreversible pulpitis. Methodology Two hundred and thirty‐four adult patients, diagnosed with irreversible pulpitis in a mandibular tooth, participated in this multicentre, randomized double‐blinded trial. Patients received IANB with 1.8 mL of 4% articaine with 1 : 100 000 epinephrine. Pain during treatment was recorded using the Heft–Parker visual analogue scale (HP VAS). The primary outcome measure, and the definition of 'success', was the ability to undertake pulp chamber access and canal instrumentation with no or mild pain (HP VAS score <55 mm). Patients who experienced 'moderate‐to‐severe' pain (HP VAS score ≥55 mm) were randomly allocated into two groups and received buccal infiltrations with either 1.8 mL or 3.6 mL of 4% articaine with 1 : 100 000 epinephrine. Root canal treatment was re‐initiated after 10 min. Success was again defined as no pain or weak/mild pain during endodontic access preparation and instrumentation. Statistical analysis was performed using Mann–Whitney U and chi‐square tests. Results The initial IANB of 4% articaine gave an overall success rate of 37%. The success rate of supplementary buccal infiltration with 1.8 and 3.6 mL volumes was 62% and 64%, respectively. The difference between the success rates of the two volumes was not statistically significant. Conclusions Increasing the volume of 4% articaine with 1 : 100 000 epinephrine from 1.8 to 3.6 mL, given as supplementary buccal infiltrations after a failed primary IANB with 1.8 mL of 4% articaine with 1 : 100 000, did not improve the anaesthetic success rates in patients with symptomatic irreversible pulpitis.